Analysis of the Impact of Increased Prices of Basic Necessities on Per Capita Income in Indonesia: A Review from a Domestic Economic Perspective - Supardi; Sriyono; Mohammad Rizal Yulianto (Antis Publisher, 2024)
The increase in prices of basic necessities has a significant impact on a country's per capita income. This research aims to analyze the impact of rising prices of basic necessities on per capita income in Indonesia, with an emphasis on the domestic economic perspective. The panel data regression analysis method is used to evaluate the relationship between increases in prices of basic necessities and per capita income, by controlling for various other economic and demographic factors. The research results show that the increase in prices of basic necessities has a real influence on per capita income in Indonesia. A decrease in purchasing power due to an increase in the price of basic necessities can reduce the real income of individuals and families, which in turn affects overall per capita income. The impact is felt especially among households with low income levels. Other factors such as inflation, economic growth and government policies also play a role in determining the impact of rising prices of basic necessities on per capita income. Therefore, there is a need for appropriate policies to effectively manage rising prices of basic necessities, including steps to control inflation, strengthen the social protection system, and increase economic productivity. In conclusion, the increase in prices of basic necessities has significant implications for per capita income in Indonesia. A holistic and sustainable approach is needed in formulating economic policies that can overcome these challenges, taking into account various external and internal factors that influence domestic economic dynamics.